2018
DOI: 10.3892/mmr.2018.8594
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma‑associated genes identified by integrative analysis of gene expression data

Abstract: Cholangiocarcinoma (CCA) is characterized by delayed diagnosis and poor survival rate. Research efforts have focused on novel diagnostic technologies for this type of cancer. Transcriptomic microarray technology is a useful research strategy for investigating the molecular properties of CCA. The objective of the present study was to identify candidate biomarkers with high potential for clinical application in CCA using a meta-analysis-based approach. Gene expression profiles of CCA were downloaded from the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the last few decades, gene profiling [ 12 , 13 , 14 , 15 ] and clinical histopathology [ 16 , 17 , 18 , 19 , 20 ] studies have greatly added to our knowledge of the genes and molecular pathways that are involved in the pathogenesis and progression, and define the prognosis, of CCA. The top genes that were found to be abnormally expressed in CCA, with a frequency ranging from 10% to >50 depending on the topographical location (intra or extrahepatic), the population studied, and the method include TP53 , KRAS , CDKN2/p16 INK4 , FGFR2 gene fusions, ERBB2 , IDH1 , and ARID1A [ 12 , 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, gene profiling [ 12 , 13 , 14 , 15 ] and clinical histopathology [ 16 , 17 , 18 , 19 , 20 ] studies have greatly added to our knowledge of the genes and molecular pathways that are involved in the pathogenesis and progression, and define the prognosis, of CCA. The top genes that were found to be abnormally expressed in CCA, with a frequency ranging from 10% to >50 depending on the topographical location (intra or extrahepatic), the population studied, and the method include TP53 , KRAS , CDKN2/p16 INK4 , FGFR2 gene fusions, ERBB2 , IDH1 , and ARID1A [ 12 , 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to discrete early clinical symptoms, lack of sensitive and speci c markers, and limited diagnostic methods patients are often treated during the middle and late stages of disease. The survival rate has not improved much in recent years [27,28]. Therefore, determining the key molecules causing liver cancer, exploring its internal mechanisms and nding potential therapeutic targets are future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC presents a significant inter-tumor and an intra-tumor heterogeneity and based on patterns of gene expression profiling, researchers classified PDAC into sub-groups with different molecular features such as (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine, that reflect a different clinical behavior with a potential for specific personalized treatment[134-136]. Genomic profiling studies have highlighted distinct subtypes also regarding CCA[137], some evidences demonstrated two main classes: the inflammation and the proliferation, with the latter being associated with worse outcome compared to the inflammation class[138]. In addition, in the past few years, an increasing attention has been paid on the potential role of noncoding RNAs (ncRNAs), classified according to their length into long (> 200 nucleotides) and small (18 to 200 nucleotides), for their involvement in cell proliferation, growth, tumor progression and drug resistance of several tumors[139,140].…”
Section: Cholangiocarcinoma and Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%